IMAGING DIAGNOSIS – SEMINOMA CAUSING LIVER COMPRESSION IN A SPUR‐THIGHED TORTOISE (TESTUDO GRAECA). Issue 2 (10th February 2014) - Pees, Michael; Ludewig, Eberhard; Plenz, Bastian; Schmidt, Volker
<x xml:space="preserve">Abstract</x> A 13‐year‐old male spur‐thighed tortoise (Testudo graeca) was presented with anorexia, apathy, and prolapse of penile tissue. Ultrasonography revealed a large heterogeneous mass in the coelomic cavity, and fine‐needle aspiration demonstrated sperm. Magnetic resonance imaging showed a sharply defined mass originating from the left testis. Appearance and signal intensities were similar to those reported in testicular neoplasms in humans, in particular sharing similarities with seminomas. Necropsy results and histopathological findings were consistent with a seminoma. To the authors' knowledge this is the first report of the diagnosis of testicular neoplasia in a reptile using imaging techniques.